Geroneuroprotectors: Effective Geroprotectors for the Brain - Schubert, David (Trends Pharmacol Sci, 2018)
Geroprotectors are compounds that slow the rate of biological aging and therefore may reduce the incidence of age-associated diseases such as Alzheimer’s disease (AD). However, few have therapeutic efficacy in mammalian AD models. Here we describe the identification of geroneuroprotectors (GNPs), novel AD drug candidates that meet the criteria for geroprotectors.